2017
DOI: 10.5539/elt.v10n5p81
|View full text |Cite
|
Sign up to set email alerts
|

The Indonesian EFL Learners’ Motivation in Reading

Abstract: The motivation will drive the EFL learners to be successful in reading. This study examined the Indonesian EFL learners' motivation in reading activity based on Deci and Ryans' theory of motivation including intrinsic and extrinsic. This study employed mixed-method design. The data obtained by distributing questionnaire and arranging the group interviewed. The subject of the study involved 42 freshmen students of English department, the faculty of humanities at Jember University in the academic year 2015-2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 6 publications
6
51
1
4
Order By: Relevance
“…Attitude towards reading is a complex construct that composes of elements such as prevailing feelings about reading, action readiness for reading and evaluative beliefs about reading (Chapman & Tunmer, 1995;Guthrie et al, 2007;McKenna, Conradi, Lawrence, Jang, & Meyer, 2012;Muijs, 1997). Prior research suggests that intrinsic motivation, a term that is sometimes used as a synonym for enjoyment of reading in some past studies, is a strong predictor of reading engagement which in turn influences reading achievement (Clark & De Zoysa, 2011;Cox & Guthrie, 2001;Guthrie & Wigfield, 2000;Malanchini et al, 2017;Salikin, Bin-Tahir, Kusumaningputri, & Yuliandari, 2017). Motivation itself is a complex multidimensional concept composing of elements such as self-efficacy, interest, preference for challenge and social interaction (Baker & Wigfield, 1999;Metsäpelto et al, 2017;Morgan & Fuchs, 2007;Ryan & Deci, 2000;Swalander & Taube, 2007;Seitz, 2010;Stutz, Schaffner, & Schiefele, 2017).…”
mentioning
confidence: 99%
“…Attitude towards reading is a complex construct that composes of elements such as prevailing feelings about reading, action readiness for reading and evaluative beliefs about reading (Chapman & Tunmer, 1995;Guthrie et al, 2007;McKenna, Conradi, Lawrence, Jang, & Meyer, 2012;Muijs, 1997). Prior research suggests that intrinsic motivation, a term that is sometimes used as a synonym for enjoyment of reading in some past studies, is a strong predictor of reading engagement which in turn influences reading achievement (Clark & De Zoysa, 2011;Cox & Guthrie, 2001;Guthrie & Wigfield, 2000;Malanchini et al, 2017;Salikin, Bin-Tahir, Kusumaningputri, & Yuliandari, 2017). Motivation itself is a complex multidimensional concept composing of elements such as self-efficacy, interest, preference for challenge and social interaction (Baker & Wigfield, 1999;Metsäpelto et al, 2017;Morgan & Fuchs, 2007;Ryan & Deci, 2000;Swalander & Taube, 2007;Seitz, 2010;Stutz, Schaffner, & Schiefele, 2017).…”
mentioning
confidence: 99%
“…Learners' reading habit are established if they live in a good literacy environment , regular reading motivation and habits in L1, and access to digitalized texts and literary texts (Iftanti, 2015). Besides, the more experiences the students have in reading English texts, the more they desire to read English texts (Salikin et al, 2017). It shows that learners increase reading competency through extensive reading (Milliners, 2017).…”
Section: Extensive Readingmentioning
confidence: 99%
“…Yamashita (2015) claimed that positive attitude and motivation encourage extensive reading and continued engagement in reading. Salikin, Bin-Tahir, Kusumaningputri, and Yuliandari (2017) found that both intrinsic and extrinsic motivations have significant impact on motivating the learners to read English. However, Meniado (2016) claimed that there is no correlation between reading motivation and reading comprehension, which contradicts previous findings of most studies.…”
Section: Reading Motivation In Efl Readingmentioning
confidence: 99%